2017 IEEE Global Humanitarian Technology Conference (GHTC) 2017
DOI: 10.1109/ghtc.2017.8239226
|View full text |Cite
|
Sign up to set email alerts
|

A global market assessment methodology for small wind in the developing world

Abstract: Abstract-Locally Manufactured Small Wind Turbines (LMSWTs) are growing in recognition as a means for rural electrification, and for meeting sustainability and poverty reduction targets set by the UN. This assessment is intended to inform governments and supranational entities where best to invest in order to meet these UN targets and improve the quality of life for millions of people in rural areas. This paper outlines the methodology used in the market assessment and discusses how the information and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…SWTs can generate the energy required by rural homes, farms (Ahshan et al, 2018;Verde et al, 2018), schools/ campuses, and medium-sizes businesses in regions where the average wind speed is high and the grid infrastructure is limited (Artal-Sevil et al, 2018). According to global investigations (Alsop et al, 2017), these regions need energy production by systems such as SWTs. Experiments conducted in some countries, such as Oman (Ahshan et al, 2018), Ethiopia, and Nepal (Latoufis et al, 2018), have demonstrated the practicality of SWTs.…”
Section: Introductionmentioning
confidence: 99%
“…SWTs can generate the energy required by rural homes, farms (Ahshan et al, 2018;Verde et al, 2018), schools/ campuses, and medium-sizes businesses in regions where the average wind speed is high and the grid infrastructure is limited (Artal-Sevil et al, 2018). According to global investigations (Alsop et al, 2017), these regions need energy production by systems such as SWTs. Experiments conducted in some countries, such as Oman (Ahshan et al, 2018), Ethiopia, and Nepal (Latoufis et al, 2018), have demonstrated the practicality of SWTs.…”
Section: Introductionmentioning
confidence: 99%
“…To generate the methodology presented here, market assessments for stand-alone renewable energy systems for PUE applications have been reviewed, including (Alsop et al, 2017;Eales et al, 2017;Smith et al, 2019;Sumanik-Leary et al, 2016). These assessments typically use strategic indicators such as distance to grid, population density, accessibility, and economic activities, alongside surveys and questionnaires to answer socio-economic questions including current and expected energy use estimation, ability, and willingness to pay, existing and aspirational business activity and other social and demographic indicators.…”
Section: Methodsmentioning
confidence: 99%
“…Fostering the development of a small wind industry based on local manufacture requires stable institutional support, as evidence from successful initiatives suggests [23]. More specifically, institutional support may be needed to create market opportunities for local manufacturers, to provide the physical infrastructure required for the LMSWTs to work properly, to develop standards and guidelines related to the operation and maintenance of LMSWTs [48], to conduct research and development [23], and to ensure adequate ancillary services, such as supply chain, maintenance network, and local capacity [49]. Considering the institutional changes needed for LMSWTs to be effectively implemented in local contexts, DM-L1 and DM-L2 were assigned high values of institutional burden.…”
Section: Calculation Of Sustainability Indicatorsmentioning
confidence: 99%
“…and to ensure adequate ancillary services, such as supply chain, maintenance network, and local capacity [49]. Considering the institutional changes needed for LMSWTs to be effectively implemented in local contexts, DM-L1 and DM-L2 were assigned high values of institutional burden.…”
Section: Calculation Of Sustainability Indicatorsmentioning
confidence: 99%